Reverse Conversion of Signed – Digit Number System: Fast Transformation of Sign – Magnitude Output - Chakraborty, MS (International Journal of Computer Sciences and Engineering, 2025)
In spite of various advantages of using signed – digit number system, so far reverse conversion has remained a major performance bottleneck of signed – digit arithmetic. Yet, the sign – magnitude output algorithm(s) for reverse conversion of signed – digit number system is known to be extensible to provide radix – complement output at constant additional time. In other words, the additional delay due to the carry that may otherwise propagate once again, may be easily eliminated. This is supposed to nullify the negative aspects of reverse conversion on arithmetic units working on signed – digit number system in longer run. Thus significant performance enhancement of signed – digit number system(s) may be possible. However, as shown in this paper, the existing digit – parallel algorithm for sign – magnitude to radix – complement output transformation can not work correctly. So a modified scheme is proposed and its correctness is proved.